In Vitro Skin Permeation of Idebenone from Lipid Nanoparticles Containing Chemical Penetration Enhancers - Lucia Montenegro; Ludovica Maria Santagati; Maria Grazia Sarpietro; Francesco Castelli; Annamaria Panico; Edy Angela Siciliano; Francesco Lai; Donatella Valenti; Chiara Sinico (MDPI AG, 2021)
Lipid nanoparticles (LNPs) have been proposed as carriers for drug skin delivery and targeting. As LNPs effectiveness could be increased by the addition of chemical penetration enhancers (PE), in this work, the feasibility of incorporating PE into LNPs to improve idebenone (IDE) targeting to the skin was investigated. LNPs loading IDE 0.7% w/w were prepared using hydrophilic (propylene glycol, PG, 10% w/w or N-methylpyrrolidone, NMP, 10% w/w) and/or lipophilic PE (oleic acid, OA, 1% w/w; isopropyl myristate, IPM, 3.5% w/w; a mixture of 0.5% w/w OA and 2.5% w/w IPM). All LNPs showed small sizes (<60 nm), low polydispersity index and good stability. According to the obtained results, IDE release from LNPs was not the rate-limiting step in IDE skin penetration. No IDE permeation was observed through excised pigskin from all LNPs, while the greatest increase of IDE penetration into the different skin layers was obtained using the mixture OA/IPM. The antioxidant activity of IDE-loaded LNPs, determined by the oxygen radical absorbance capacity assay, was greater than that of free IDE. These results suggest that the use of suitable PE as LNPs components could be regarded as a promising strategy to improve drug targeting to the skin.